2021
DOI: 10.1038/s41598-021-99798-5
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation is the turning point for the spreading of a weedy epiphyte: an IBM approach

Abstract: The rapid spread of many weeds into intensely disturbed landscapes is boosted by clonal growth and self-fertilization strategies, which conversely increases the genetic structure of populations. Here, we use empirical and modeling approaches to evaluate the spreading dynamics of Tillandsia recurvata (L.) L. populations, a common epiphytic weed with self-reproduction and clonal growth widespread in dry forests and deforested landscapes in the American continent. We introduce the TRec model, an individual-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 109 publications
1
16
0
1
Order By: Relevance
“…Evidence has shown that inbreeding depression and population differentiation then become more likely, under the pressure of sustained dispersal limitations between isolated populations (Wright et al 2013). As such, low connectivity would be expected in urban landscapes, as well as high spatial genetic structure (SGS) (Chaves et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence has shown that inbreeding depression and population differentiation then become more likely, under the pressure of sustained dispersal limitations between isolated populations (Wright et al 2013). As such, low connectivity would be expected in urban landscapes, as well as high spatial genetic structure (SGS) (Chaves et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The majority (24 or 80%) of them have discussed epiphyte population genetics in the context of microsatellite marker cross-ampli cation and species biology. The remaining papers (6 or 20%) investigated the population genetics of epiphytes in relation to fragmented landscapes, such as rural sites (Chaves et al 2018(Chaves et al , 2021; Aoki-Gonçalves et al 2020), industrial mining sites (Lavor et al 2014) and modi ed natural forests or reserves (Alcantara et al 2006;Goetze et al 2015). From these six aforelisted papers, contrasting outcomes of landscape fragmentation were reported for epiphyte genetic structure, largely dictated by the variety of taxonomic groups and breeding strategies that have been described.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations